Strength and conditioning in a Covid-19 world - Dalla Pace, L.; Geneau, M.-C.; O`Mahony, D. (Canadian Sport Institute, 2020)
What can we do during Covid-19? • Aim to identify most demanding aspects of sport and load/train as best as possible. • Develop physical qualities which may not be optimally developed in sport or are absent due to training cessation • Train general modalities -phase potentiation/recovery when sport resumes • Focus on what we can do and can control -keep goal of return to sport in mind